ALEXANDER Ya. ORLOV - WELL-KNOWN SCIENTIST AND RECOGNIZED ORGANIZER OF ASTRONOMICAL RESEARCH. LITTLE-KNOWN FACTS OF HIS LIFE - Yatskiv, Ya. S.; Vavilova, I. V.; Korsun, A. A. (Одеські астрономічні публікації, 2012)
Alexander Ya. Orlov is a well-known astronomer and geophysicist as well as a worldrecognized organizer of scientific research in Russia, the USSR, and Ukraine. Orlov has formulated his main scientific ideas during the Odesa's period of life. He studied a tidal deformation of the Earth and its polar motion using the gravity and latitude observations. He has proposed new defenitions of a mean pole and a mean latitude, as wel as a new method for determing the Earth pole coordinates. To the end of 1940-ties, the Orlov's scientific ideas were implemented and stimulated a development of a research field, which is now called as Astrogeodynamics or Space Geodynamics. Among the representatives of the Orlov's scientific school are about 20 Doctors of Sciences and more than 40 Candidates of Sciences, including the members of Academy of Sciences of Ukraine and other countries. Among them are N.Stoyko-Radilenko (France), J.Witkowski (Poland), V.Zhardetsky (Yugoslavia-Austria-USA), D.Pyaskovsky, Z.Aksent'eva, E.Lavrentieva, N.Popov, E.Fedorov and A.Korol in Ukraine. The deserved followers of the Orlov's scientific ideas were also I.Androsov, I.Dyukov, K.Mansurova, B.Novopashennyj, N.V.Zimmerman in Russia and M.Bursa (Chesh Republic), who worked with him, as well as his sons, A.A.Orlov and B.A. Orlov. The Orlov's life and scientific activity were fully described in many articles. For that reason in this paper we will focus on the little-known facts of the Orlov's scientific-organizational activity, for example, the Orlov's appointments as a director of observatories in Odesa, Poltava, m.Pip-Ivan, Pulkovo, and Kyiv; interesesting facts related to his membership in the Academies of Sciences of the USSR and Ukrainian SSR; organization of a large-scale program on the latitude observations and gravimetric survey. We describe briefly his life and his astrogeodynamic scientific school.